Role of intellectual innovation in the EU states - Gierańczyk, Wiesława (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2010)
The world development is characterized by blurring the division between science and economy. As a result, industrial development based on a growing dependency on knowledge and information has accelerated. In turn, due to the development of the knowledge-based economy, the importance of the so-called intellectual property laws is also on the increase. Protection of these laws not only constitutes one of the main branches of the market, but also remains a transaction object. This way cooperation between science and industry finds its realization. It enables the partners to gain dominance on the market and leads to creating new solutions which further power technological progress.